Water Quality After Removing Shops at Klong Ong Ang - สมพงษ์, อุทุมพร (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2018)
Klong Ong Ang is a historical canal in Bangkok. There were shops trespassing the canal over 30 years. It affected to drainage and water pollution, so Bangkok used law to remove the shops in 2015. Therefore, this research is for studying factors that affected to water quality of Klong Ong Ang viz. removing the shops, month and floodgate, and identifying type of surface water by studying water quality of the canal viz. color, odor, turbidity, dissolved oxygen (DO), biochemical oxygen demand (BOD), total coliform bacteria (TCB) and fecal coliform bacteria (FCB). We collected 3 times within 6 months. The collection was 2 times, before opening and after closing Ong Ang floodgate. It was found that the 1 and 3 months-water samples were green, turbid, and odorless, while the 6 month-water was colorless, clear, and odorless. Moreover, DO was 3.12 - 5.49 mg/L, BOD was 4.39 - 14.03 mg/L, TCB was 1.95 x 105 - 1.95 x 106 MPN/100 mL, and FCB was 6.65 x 104 - 6.37 x 105 MPN/100 mL. Besides, DO and FCB were higher than those of before removing the shops in 1983, 1998, and 2012 at 0.05 significant level. DO was in standard level, while FCB was out of the level. WQI (Water Quality Index) was 24.01, so Klong Ong Ang should be surface water type 5 that can be used for only transportation following standard of surface water.